2020
DOI: 10.14207/ejsd.2020.v9n3p313
|View full text |Cite
|
Sign up to set email alerts
|

Saving Water for the Future Via Increasing Plant Literacy of Pupils

Abstract: The struggle for mitigation of global climate changes is aimed mostly on CO2 emissions, while the role of vegetation having strong impact on water retention in the landscape and cooling of environment stays out of the focus. The reason is human illiteracy of plant role in our environment having roots already in school education. The vegetation use the majority of solar energy for the water evaporation from leaves and by this way cools itself as well as environment and increase water retention in the landscape.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Accordingly, these factors contribute to enhancing the student knowledge of the schoolyards tree species and therefore increase the students' botanical literacy as noted by [43,44]. Since the study revealed that most students had low botanical knowledge of the tree species existing in their schoolyards, this might pose a serious hindrance to the students' discussion about tree species, which can affect negatively the student's observational skills and conceptual learning as noted by [45,46]. Furthermore, poor botanical knowledge could augment the risk of the students consuming toxic fruits [47].…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, these factors contribute to enhancing the student knowledge of the schoolyards tree species and therefore increase the students' botanical literacy as noted by [43,44]. Since the study revealed that most students had low botanical knowledge of the tree species existing in their schoolyards, this might pose a serious hindrance to the students' discussion about tree species, which can affect negatively the student's observational skills and conceptual learning as noted by [45,46]. Furthermore, poor botanical knowledge could augment the risk of the students consuming toxic fruits [47].…”
Section: Discussionmentioning
confidence: 96%
“…The energy distribution function of the hydrological cycle is well known by experts, however there is limited public awareness of this fact and about the magnitude of the climatic energy that is being distributed [4]. Evapotranspiration (ET) has a key role in transporting energy by picking it up as latent heat from the surface and deploying it in the clouds via condensation.…”
Section: Key Conceptsmentioning
confidence: 99%
“…The potential impacts extend to the level of funding allocated to plant conservation efforts (Balding & Williams, 2016), plant science research and enhanced participation in plant‐focused citizen science projects. To raise plant awareness and appreciation, an impressive diversity of approaches promoting botany in educational settings, as well as outside the classroom, has been proposed and developed (Crisci et al, 2020; Fančovičová & Prokop, 2011; Friesner et al, 2021; Jose et al, 2019; Levesley et al, 2012; McDonough Mackenzie et al, 2020; Moores et al, 2021; Pany et al, 2019; Thorogood, 2020; Woodland, 2007) with many demonstrating a measurable increase in botanical literacy among participants (Pinkerton et al, 2021; Ryplova & Pokorny, 2020; Stagg & Donkin, 2013; Wells et al, 2021). The growing number of initiatives run by plant scientists, such as international Fascination of Plants Day (https://plantday18may.org/), PlantLoveStories (https://www.plantlovestories.com) or More Than Weeds (https://morethanweeds.co.uk/), as well as relentless work of botanical gardens around the world, also continues to promote an awareness and appreciation of plants among the general public.…”
Section: Challenge: the End Of Botany?mentioning
confidence: 99%